Calcium Signals in Astrocyte Microdomains, a Decade of Great Advances - Lia, Annamaria; Henriques, Vanessa Jorge; Zonta, Micaela; Chiavegato, Angela; Carmignoto, Giorgio; Gómez-Gonzalo, Marta; Losi, Gabriele (Frontiers in Cellular Neuroscience, 2021)
The glial cells astrocytes have long been recognized as important neuron-supporting elements in brain development, homeostasis, and metabolism. After the discovery that the reciprocal communication between astrocytes and neurons is a fundamental mechanism in the modulation of neuronal synaptic communication, over the last two decades astrocytes became a hot topic in neuroscience research. Crucial to their functional interactions with neurons are the cytosolic Ca2+ elevations that mediate gliotransmission. Large attention has been posed to the so-called Ca2+microdomains, dynamic Ca2+ changes spatially restricted to fine astrocytic processes including perisynaptic astrocytic processes (PAPs). With presynaptic terminals and postsynaptic neuronal membranes, PAPs compose the tripartite synapse. The distinct spatial-temporal features and functional roles of astrocyte microdomain Ca2+ activity remain poorly defined. However, thanks to the development of genetically encoded Ca2+ indicators (GECIs), advanced microscopy techniques, and innovative analytical approaches, Ca2+ transients in astrocyte microdomains were recently studied in unprecedented detail. These events have been observed to occur much more frequently (∼50–100-fold) and dynamically than somatic Ca2+ elevations with mechanisms that likely involve both IP3-dependent and -independent pathways. Further progress aimed to clarify the complex, dynamic machinery responsible for astrocytic Ca2+ activity at microdomains is a crucial step in our understanding of the astrocyte role in brain function and may also reveal astrocytes as novel therapeutic targets for different brain diseases. Here, we review the most recent studies that improve our mechanistic understanding of the essential features of astrocyte Ca2+ microdomains.